The Strands and Findings of Recent Research on Technology-enhanced Collaborative Writing in EFL Settings: A Systematic Review - Pardede, Parlindungan (JET (Journal of English Teaching), 2024)
More and more researchers and educators have recently focused their attention to technology-enhanced collaborative writing (TECW) in English as a Foreign Language (EFL) setting. Yet, the updated review focusing on research in this field is meager. This study aims at helping researchers and educators get a deeper understanding of the features and development tendencies of recent research on TECW in EFL setting. It systematically reviewed 45 empirical studies published from 2014 to 2023, focusing on strands and findings. In terms of research strands, the results showed the writing process, outcomes, and students and teachers’ perceptions and attitudes. In terms of research findings, the review results showed that TECW was effective in enhancing students’ writing performance, developing a sense of community, engagement, motivation, collaboration, and satisfaction. The studies’ findings also revealed that students and teachers demonstrated a strong disposition towards TECW practices.